2020
DOI: 10.3390/mti4030065
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Training in Visual Block Programming for Preservice Teachers

Abstract: This study evaluates the effectiveness of visual block programming-based instruction and its possibilities in the training of future teachers. In particular, the application Scratch, a visual programming environment, was employed to introduce pre-service teachers to programming. The study followed a mixed-method design with a sample of 79 pre-service teachers. A quantitative approach was used to evaluate the gains in the participants’ knowledge of computational concepts and attitudes towards Scratch as a pedag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…To conclude, Sáez-López et al [57] found that Scratch resulted in significant improvements in innovation, collaboration, active learning, and motivation for prospective teachers. Schmidt-Crawford et al [58] reported that coding experiences through Scratch and programs similar to it, such as Scratch Junior and Code.org that teach coding, evolves into a commonplace activity for both prospective and in-service teachers.…”
Section: Discussionmentioning
confidence: 95%
“…To conclude, Sáez-López et al [57] found that Scratch resulted in significant improvements in innovation, collaboration, active learning, and motivation for prospective teachers. Schmidt-Crawford et al [58] reported that coding experiences through Scratch and programs similar to it, such as Scratch Junior and Code.org that teach coding, evolves into a commonplace activity for both prospective and in-service teachers.…”
Section: Discussionmentioning
confidence: 95%
“…After receiving training, the CT ability of pre-service teachers significantly improved, which was reflected in their better understanding of CT concepts, critical thinking, innovation abilities, abstraction abilities, and so on (Pala & Mıhçı Türker, 2021 ; Saez-Lopez et al, 2020 ). Overall, interventions in 38 studies were found to be effective based on pre- and post-trial data presented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…18–40 years old CT course Critical thinking creative thinking problem solved programming or coding skills, scratch Esteve-Mon et al ( 2019 ) 114 Spanish preservice teachers 64% females and 36% males. The average age of participants was 20 The Educational robotics intervention Problem solved programming or coding skills CT concept scratch Dağ ( 2019 ) 26 pre-service teachers Department of Computer Education of the Faculty of Education CT course Programming or coding skills Scratch small basic alice Piedade et al ( 2020 ) 26 pre-service informatics teachers 57.6%% females and 42.4% males 22–56 years old The Educational robotics intervention Debugging CT concept algorithmic thinking Not reported Looi et al ( 2020 ) 329 preservice teachers 208 of them were trained in teaching non-STEM subjects CT seminar Algorithmic thinking problem solved programming or coding skills Not reported Sáez-López et al ( 2020 ) 79 pre-service teachers 72.2% females and 27.8% males Scratch Debugging problem solved programming or coding skills scratch Zha et al ( 2020 ) 15 preservice teachers 14 females and 1 male. 13 majored in elementary education and 2 majored in secondary education Hopscotch problem solved programming or coding skills CT concept …”
Section: Appendix Amentioning
confidence: 99%
“…While secondary school teachers may be expected to be adequately educated in their subjects and computing is usually a dedicated subject, the education of primary school teachers who usually teach several subjects without specialising on one particularly [30] has been reported to be insufficient [34]. In order to support primary school teachers it is important to improve their education to better prepare them for programming at primary schools, for example by teaching them to program with Scratch [12,32,40].…”
Section: Introductionmentioning
confidence: 99%